Menjadi Moderat dengan Pendekatan Living Values Education bagi Mahasantri - Arbi, Arbi; Herlina, Herlina; Sofiandi, Sofiandi; Hanafi, Imam; Hasanah, Nur (Lembaga penelitian dan pengabdian kepada masyrakat, 2024)
Currently, the Muslim community in Indonesia is experiencing a 'conservative turn.' Several radical group movements seem to be expanding their roles in various dimensions of community life, including education. Many surveys corroborate this condition. The symptoms of intolerance have also entered the activities at Ma’had Al-Jamiah UIN Suska Riau, an